PENINGKATAN KOMPETENSI PEDAGOGIK GURU PAUD MELAUI MEDIA AUDIO VISUAL PADA MASA PANDEMI COVID-19 - Heti Rukmini; Agus Sumitra; Sharina Munggaraning Westhisi (IKIP Siliwangi, 2022)
This research is motivated by the facts that occurred in Bakti Asih Kindergarten during the Covid-19 pandemic, namely teachers were confused about how to learn the right way during this pandemic due to the teacher's lack of mastery of technology. In this case, the Foundation organizes training for PAUD teachers regarding the making of learning videos in order to increase pedagogic competence. This study aims to describe improving the pedagogic competence of PAUD teachers through audio-visual media during the Covid-19 pandemic. The research subjects were five teachers at Bakti Asih Kindergarten, Bandung. The type of research used is descriptive qualitative, where data collection is carried out namely observation, interviews, and questionnaires. Data analysis is in the form of data reduction activities, data display, and conclusion drawing. The results showed that of the five kindergarten teachers at Bakti Asih Kindergarten, three teachers already understood and mastered technology very well and two teachers still needed help with obstacles they still did not understand and lacked knowledge of technology. This shows that the pedagogic improvement of PAUD teachers in audio-visual media is very much needed. Teachers respond well and are motivated to continue to improve their pedagogical abilities so that online learning that is carried out remains fun and not boring for children.Penelitian ini dilatarbelakangi oleh fakta yang terjadi di TK Bakti Asih selama masa pandemi Covid-19, yaitu guru kebingungan menentukan bagaimana cara belajar yang tepat pada masa pandemi ini dikarenakankurangnya penguasaan ilmu teknologi yang dimiliki oleh guru. Dalam hal ini Yayasan menyelenggarakan pelatihan bagi guru PAUD mengenai pembuatan video pembelajaran dalam rangka peningkatan kompetensi pedagogik. Penelitian ini bertujuan untuk mendeskripsikan peningkatan kompetensi pedagogik guru PAUD melalui media audio visual dimasa pandemi Covid-19. Adapun subjek penelitian lima orang guru di TK Bakti Asih Bandung. Jenis penelitian yang digunakan deskriptif kualitatif, dimana pengumpulan data yang dilakukan yaitu observasi, wawancara dan angket. Analisis data berupa aktifitas reduksi data, display data dan penarikan kesimpulan. Hasil penelitian menunjukkan dari lima orang guru taman kanak-kanak di TK Bakti Asih tiga orang guru sudah paham serta menguasai betul tentang ilmu teknologi dan dua orang guru masih memerlukan bantuan dengan kendala masih belum paham dan kurang menguasai ilmu teknologi . Hal ini menunjukkan peningkatan pedagogik guru PAUD media audio visual sangat di perlukan. Guru merespon dengan baik dan termotivasi untuk terus meningkatkan kemampuan pedagogiknya agar pembelajaran daring yang dilaksanakan tetap menyenangkan dan tidak membosankan bagi anak.